THE INFLUENCE OF IN DEPTH LEARNING ON STUDENTS MOTIVATION AND LEARNING INDEPENDENCE AT PADANGSIDIMPUAN STATE ELEMENTARY SCHOOL 200306 - Siti Rahma Sianipar; Hairul Idris; Hamka (PT. Jurnal Center Indonesia Publisher, 2026)
Abstract This study aims to analyze the effect of the implementation of immersive learning on student motivation and learning independence at Padangsidimpuan Public Elementary School 200306. The background of this research stems from the need to provide a learning process that is not only oriented towards final results, but also encourages students to understand the meaning of learning, think critically, and take responsibility for their learning process. The research method used was a quantitative approach with a quasi-experimental design. The study subjects included 50 fifth-grade students divided into an experimental group and a control group. Data collection instruments included a learning motivation questionnaire, a learning independence observation sheet, and documentation of learning outcomes. Data were analyzed using a t-test to determine significant differences between the two groups. The results showed that the implementation of immersive learning had a positive and significant impact on increasing student motivation and learning independence. Students participating in immersive learning demonstrated greater enthusiasm, active question-asking, and the ability to manage assignments independently compared to those in the control group. These findings indicate that immersive learning strategies can be an effective alternative in developing reflective, independent, and problem-solving-oriented learners. Thus, the implementation of immersive learning in elementary schools needs to be continuously strengthened through teacher training, the development of teaching materials, and a learning culture that fosters students' ongoing curiosity.